Characteristics of non-diabetic foot ulcers in Western Sydney, Australia. Issue 1 (December 2016) - Haji Zaine, Norafizah; Hitos, Kerry; Vicaretti, Mauro; Fletcher, John; Begg, Lindy; Burns, Joshua
Abstract Background There are few studies investigating the characteristics, risk factors and socioeconomic status of patients with non-diabetic foot ulcers. The aim of this study was to explore the characteristics of non-diabetic foot ulcers in a large tertiary referral outpatient hospital setting in Western Sydney, Australia. Methods From 2011 to 2013, data from 202 patients with non-diabetic foot ulcers during their initial visit were retrospectively extracted for analysis from Westmead Hospital's Foot Wound Clinic Registry. Data including demographics, socioeconomic status and foot ulcer characteristics were recorded on a standardised data collection form. Results Demographics and physical characteristics were: 54 % male, median age 78 years [interquartile range (IQR): 64–87], median body mass index (BMI) of 23.8 kg/m2 (IQR: 20–26.9), 35 % had loss of protective sensation and the median postcode score for socioeconomic status was 996 (IQR: 935–1034). Foot ulcer characteristics were: median cross-sectional area of 1.2 cm2 (IQR: 0.3–5.0), 30.5 % plantar and 27 % dorsal, 22.1 % University of Texas (UT) Wound Classification for Diabetic Foot Ulcers Grade of 1C-3C (with ischaemia). Conclusions Unlike diabetic foot ulcers, non-diabetic foot ulcers largely affected older malesand females. In accordance with diabetic foot ulcer characteristics, socioeconomic status was not related to non-diabetic foot ulcers in Western Sydney. Based on the findings of this study the epidemiological pattern of non-diabetic foot ulceration and its pathogenesis requires further investigation.